Pre-schoolers' tooth brushing behaviour and association with their oral health: a cross sectional study - Iqra Muhammad Khan; Shani Ann Mani; Jennifer Geraldine Doss; Mahmoud Danaee; Lydia Yi Li Kong (BMC, 2021)
Abstract Background Toothbrushing is an important yet neglected behaviour that affects the oral health of preschool children. Little is reported on parental supervision, an essential aspect of routine effective toothbrushing in this age group. The aim of this study was to evaluate pre-schoolers' toothbrushing behaviour including parental involvement and its association with their oral health. Methods This was a cross-sectional study. A total of 92 preschool children (4-6 years) were invited to participate with their parents/guardians. Nine parameters of toothbrushing behaviour were assessed from parental responses (questionnaire) and observation of child and parents/guardians (video recording). Oral examination included recording plaque, gingival and dental caries indices. BORIS software was used to assess toothbrushing parameters and Smart PLS was used to perform association with a second-generation multivariate analysis to create models with and without confounding factors. Results Girls were slightly more (53%) than boys (47%). Children aged 4 years were slightly more in number (38%), followed by 6-year-olds and 5-year-olds. Nearly, 90% parents had tertiary education and 46% had more than 2 children. Differences were recorded in the reported and observed behaviour. Thirty-five percent parents/guardians reported using pea-size toothpaste amount but only 28% were observed. Forty percent reported to brush for 30 s-1 min, however 51% were observed to brush for 1-2 min. Half the children were observed to use fluoridated toothpaste (F < 1000 ppm) under parental supervision (11%). The mean (SD) plaque score reduction after toothbrushing was 10.80 (2.46), mean pre-brushing plaque score was 90.3 (10.2), mean gingival index was 0.89 (0.65) and mean dental caries status (ICDAS(1-6)) was 18.87 (12.39). Toothbrushing behaviour in terms of toothbrushing technique, duration, pattern and frequency, toothbrush type and grip type, toothpaste type and amount, post-brushing mouth rinsing and parental involvement contributed significantly to plaque score change (86%), dental caries status (73%), gingival index (66%) and pre-brushing plaque score (31%). The significant confounding variables had a small influence on oral health of preschool children. Conclusions Preschool children's toothbrushing behaviour was inadequate while their oral health was poor, with a significant association between the two parameters.